2021
DOI: 10.1186/s41927-021-00183-6
|View full text |Cite|
|
Sign up to set email alerts
|

Adult onset Still’s disease in the elderly: a case-based literature review

Abstract: Background Adult onset Still’s disease (AOSD) is a rare inflammatory disorder that classically presents with high spiking fevers, evanescent rash, and arthritis. The diagnosis is one of exclusion and can be further complicated by atypical presentations, particularly in elderly patients in whom AOSD is very rare. Case presentation A case of AOSD in a 73-year-old woman with a non-classic presentation, leading to delayed diagnosis and management, is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In a recent Dutch case series of VEXAS, among patients with unclassified autoinflammation, two among the twelve retrospectively identified were initially suspected with AOSD [ 28 ]. Thus, elderly patients with late AOSD diagnosis or suspicion as described in some series [ 29 , 30 ] could also benefit from UBA1 mutation screening.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent Dutch case series of VEXAS, among patients with unclassified autoinflammation, two among the twelve retrospectively identified were initially suspected with AOSD [ 28 ]. Thus, elderly patients with late AOSD diagnosis or suspicion as described in some series [ 29 , 30 ] could also benefit from UBA1 mutation screening.…”
Section: Discussionmentioning
confidence: 99%
“…1). Suda et al [3] and Mollaeian et al [42] reported 1 case of EOSD and reviewed, from the literature, 24 and 38 cases, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The typical skin rash is an evanescent salmon-pink erythema, predominantly on the extremities, which is one of the diagnostic criteria. However, atypical skin rashes have been reported to be common in elderly-onset AOSD ( 29 , 30 ). The most frequent lesions of atypical skin rashes are persistent papules, plaques, or erythema ( 30 , 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%